Analysis Of Student Activeness In Learning Science In Sds Bina Satria Mulia - Rahmatillah, Cut Nur Aini; Siregar, Ardilla Azzahra (Journal of Innovation in Research, Education and Culture (JIREC), 2023)
This research is motivated by the lack of student activity in learning science, unsatisfactory student achievement, and lack of learning media. The Numbered Head Together (NHT) cooperative approach model is used to overcome these problems. The research subjects were fifth grade students at SDS Bina Satria Mulia. This research is included in classroom action research with planning, action, observation, and reflection steps. The results showed that the average score of student activity tended to increase significantly. In the first cycle the average score was 59%, the second cycle was 79%, and the third cycle was 90%. The next result is that teacher activity also increases. The average value sequentially is 78% in cycle 1, 88% in cycle 2, and 95% in the last cycle. The third research result is that student achievement also increases. They got an average score of 60% in the first cycle, 75% in the second cycle and 95% in the last cycle. So based on these data it can be concluded that the NHT cooperative approach can increase the activity of fifth grade students at SDS Bina Satria MuliaKeywords: Student Activity, Science Learning